Investigating potential protein markers of cardiovascular disease in children with type 1 diabetes mellitus. Issue 2 (16th April 2021) - Letunica, Natasha; CAI, Tengyi; Cameron, Fergus; Monagle, Paul; Ignjatovic, Vera; Attard, Chantal
Abstract: Background: Type 1 diabetes mellitus (T1DM) is a metabolic disease characterized by dysglycaemia. Cardiovascular disease (CVD) is a major complication among T1DM patients and the leading cause of mortality later in life. Methods: The study subjects consisted of T1DM children with poor glycemic control (HbA1c > 7.5%) and healthy age and gender matched controls. Venous blood samples were collected and tested by utilizing a novel immunoassay panel with 96 protein biomarkers. Data were analyzed using non‐linear regression analysis and the expression of biomarkers was compared between T1DM and healthy control groups using an unpaired student's t ‐test. Dynamic principal component analysis (PCA) was operated based on the differentially expressed proteins. Results: Ten T1DM children and 10 healthy controls were analyzed. Twelve CVD markers show significant differential expression between T1DM patients and healthy controls ( p < 0.05). Dynamic PCA clustering based on differentially expressed proteins demonstrated an obvious clustering between the two populations. Conclusions: This preliminary study reveals the feasibility of utilizing a novel immunoassay panel to investigate potential biomarkers for predicting incipient CVD in children with T1DM. In future, longitudinal studies are required to track the relationships between measurements of the selected protein markers and the development of CVD in T1DM patients.